Presence of choledocholithiasis in patients undergoing cholecystectomy for mild biliary pancreatitis - Pradhan, S; Shah, S; Maharjan, S; Shah, JN (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Standard recommendations for patients recovering from an episode of biliary pancreatitis include cholecystectomy with intra operative cholangiogram or ERCP during the same hospital admission as it is believed that the instigating factor is the passage of stones through the common bile duct. As ERCP is not widely available and expensive, cholecystectomy with IOC is routinely performed to rule out choledocholithiasis. However detection of common bile duct stones is challenging. Whether these patients undergoing cholecystectomy require direct common bile duct evaluation is controversial. Objective of the study was to see the presence of common bile duct stones in patients with resolving acute mild biliary pancreatitis. Methods: Patients admitted in the surgical ward in Patan Hospital and Bir Hospital with the diagnosis of mild acute biliary pancreatitis who underwent cholecystectomy with intra-operative cholangiography from August 2010 to July 2012 were studied. The outcome of cholangiogram was analyzed together with findings of common bile duct exploration. Results: A total of 52 patients with acute mild biliary pancreatitis were operated during this period. The common bile duct stone was found in 1.9%.  Out of four patients with abnormal cholangiogram, only one patient (25%) had stone on exploration, rest of the three cases (75%) had negative exploration.Conclusion: The presence of common bile duct stone in case of mild acute biliary pancreatitis undergoing cholecystectomy is very low (1.96%), and thus policy of selective IOC should be applied for cases with mild biliary pancreatitis.Journal of Society of Surgeons of Nepal Vol.17(1) 2014: 11-15